Transcriptome profiling of in vitro-matured oocytes from a korean native cow (hanwoo) after cysteamine supplementation. Issue 4 (2nd August 2021) - Chowdhury, M. M. R.; Park, Joonghoon; Afrin, Fahmida; Ko, Yeoung-Gyu; Kim, Chan-Lan; Lee, Sung Soo; Kim, Sung Woo
Abstract: This study elucidated the molecular markers that decrease oocyte quality during in vitro culture, restricting optimal developmental potential. Here, we evaluated the transcriptomic differences between cysteamine-treated and non-treated bovine cumulus oocyte complexes (COCs) after 22 h of co-culture in the maturation media using RNA sequencing. In total, 39, 014 transcripts were sequenced between cysteamine-treated and non-treated mature COCs. We evaluated the relative expression of 21, 472 genes, with 59 genes showing differential expression between the two COC groups. The cysteamine-treated group had 36 up-regulated gene transcripts and 23 down-regulated gene transcripts. Moreover, gene ontology (GO) enrichment analysis revealed that multiple biological processes were significantly enriched after cysteamine supplementation. Differentially expressed genes appeared to maintain normal oocyte physiology, regulation of apoptosis, differentiation, ossification or bone formation, cardiac and muscle physiology, hormonal secretion, and membrane construction for further embryonic development. In conclusion, cysteamine affects the mRNA level of COCs during oocyte maturation by upregulating potential molecular markers and downregulating genes that affect further embryonic development.